RECONSTRUCTION OF THE SCOPE SECURITY MANAGEMENT SYSTEM GOVERNMENT IN BONE REGENCY - Bahri, Nurmaelya; S, Syahabuddin; Sugirman, A. (Institut Agama Islam Negeri Bone, 2025)
The urgency of reconstructing the security management system within the scope of government in Bone Regency stems from the increasing complexity of governance and the evolving security challenges that threaten institutional stability and public trust. This study examines the legal foundation of the government security management system in Bone Regency, the concretization or practical implementation of the security management system, and the law enforcement of the government security management system in the region. Employing a normative-empirical legal study, this research utilizes a legislative approach, a case approach, and a conceptual approach. The legal materials analyzed include primary legal materials, secondary legal materials, and tertiary legal materials, with data collection methods consisting of observation, interviews, and documentation. Data processing and analysis are conducted through qualitative analysis to assess legal aspects and descriptive analysis to synthesize findings. The study reveals that while the security management system adheres to the principle of legality through standardized procedures based on existing laws and regulations, its practical implementation faces considerable obstacles. Limited infrastructure, technological constraints, and social disparities within institutions hinder comprehensive enforcement. Consequently, an urgent update to the security management system is necessary to foster preventive, responsive, and collaborative measures between leaders and security personnel, ensuring a more effective and resilient governance framework.